Comprehensive review on importance, challenges and future prospects of nanotechnology and combination therapy for Alzheimer’s disease - Ishrat, Nowshin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.